China's economic development strategies transformation and innovation - Liu, Rui (Singapore World Scientific, 2019)
China is a powerful engine of the global economy and the country's rise is undoubtedly the outcome of its protracted campaign of designing and implementing national development strategies since the founding of the People's Republic of China in 1949. This book reviews the transformation and innovation of China's economic development strategies, especially Deng Xiaoping's Three-Step strategy and Xi Jinping's internal and external strategies. By introducing the concept of strategic paradigm, it analyzes the theoretical basis of myriads of economic development strategies and predicts China's choice. With the evolutionary process and the outstanding problems in national development planning as the main thread, it discusses the improvement of the national planning system, specifically of the national overall planning system, the regional planning system, the interplay and conflict between regional planning. It also studies the reform of city-county planning system, major function-oriented zones (MFOZs) and planning legislation and institutionalization. It also attempts to put forward proposals to coordinate the interests of planning departments and make different types of planning at different administrative levels compatible"--
CONTENTS: CHAPTER I - The Paradigms and Schools of Economic Development Strategy - - CHAPTER II - Development Outlook and Development Strategy from A Global Perspective - - CHAPTER III - China's National Development Concept and Economic Development Strategy - - CHAPTER IV - The National Economic Development Strategy in Xi's Era - - CHAPTER V - A Historical Review of National Planning Management - - CHAPTER VI - Experiences and Lessons in Formulating National Development Plan - - CHAPTER VII - Improving Regional Planning - - CHAPTER VIII - Development Planning Reform at the County Level - - CHAPTER IX - The Planning of the Major Function-Oriented Zones: Initiation and Evolution - - CHAPTER X - Institutionalization of National Development Planning - - CHAPTER XI - Improvement and Innovation of National Development Planning System.
Keywords: Economic development -- China; China -- Economic conditions -- 1949-.; China -- Economic policy -- 1949-.